Systemic contributions to global catastrophic risk - Constantin W. Arnscheidt; S. J. Beard; Tom Hobson; Paul Ingram; Luke Kemp; Lara Mani; Alexandru Marcoci; Kennedy Mbeva; Seán S. Ó hÉigeartaigh; Anders Sandberg; Lalitha S. Sundaram; Nico Wunderling (Global Sustainability)
Abstract Non-technical summary We live in a time of significant global risk. Some research has focused on understanding systemic sources of this risk, while other research has focused on possible worst-case outcomes. In this article, we bring together these two areas of research and provide a simple conceptual framework that shows how emergent features of the global system contribute to the risk of global catastrophe. Technical summary Humanity faces a complex and dangerous global risk landscape, and many different terms and concepts have been used to make sense of it. One broad strand of research characterises how risk emerges within the complex global system, using concepts like systemic risk, Anthropocene risk, synchronous failure, negative social tipping points, and polycrisis. Another focuses on possible worst-case outcomes, using concepts like global catastrophic risk (GCR), existential risk, and extinction risk. Despite their clear relevance to each other, connections between these two strands remain limited. Here, we provide a simple conceptual framework that synthesises these research strands and shows how emergent properties of the global system contribute to the risk of global catastrophic outcomes. In particular, we show that much of GCR stems from the interaction of hazards and vulnerabilities that arise endogenously within the global system, and how ‘systems thinking’ and complex adaptive systems theory can help illuminate this. We also highlight some unique challenges that systemic sources of GCR pose for risk assessment and mitigation, discuss insights for policy, and outline potential paths forward. Social media summary The global system is generating global catastrophic risk.